Academic Senate Minutes 2001-11-08 - Academic Senate:::::::::
Agenda and Minutes approved. Special Guest Faculty Trustee Harold Goldwhite. Resolution from FSAC on Compensation for Lecturers on the Senate approved. Women's and Gender Studies as a department first reading. Follow up on Green Music Center report from Larry Furukawa-Schlereth. Green Music Center report from Jim Meyer, Director of Development. Reports fPresident of the Associated Students.